(untitled) (Fiep Bulletin - online, 2016)
The following study aims to evaluate, based on the specialized biography, the effect of practices that generates the state of good mood and what’s the influence of it in the life quality of the aimed public. To connect humor and life quality, we need to understand some key factors. The humor might influence many conditions, since physical and physiological until psychological and spiritual, enabling changes in your mood (MORAES, 2013). But, we can enlarge this definition through the practice of small daily activities that end up providing pleasure, such as: watering a plant or watching a movie, or more complex activities as an important event or a vacation trip, resulting in a good state of mind to the person, stimulating his good mood, which can be measured by the Profile of Mood States (2012).Proceeding to the next factor, the quality of life has been historically used in different ways on his domains (physical domain, psychological domain, etc). On the health domain, using a patient with degenerative disease as an example, the life quality is associated to him as an improvement of his daily activities and happier moments, favoring his life quality. However, without these other aspects, the patient is negatively influenced (MINAYO, 2000). Starting from the presupposition that life quality and god mood are closely linked, we intend to evaluate how life quality can be influenced by practices that generates a good mood. The questionnaire will be applied with individual interviews, privately, containing 65 questions. At the end of the interviews, it is expected that the results confirm the theory that good mood has a favorable effect on life quality, influencing positively the daily routine of the interviewed; finally, creating on the participants and readers of the research the desire of finding ways to keep a good mood.